Civil Law Analysis of MSME Sale Agreements via Short Messages: Analisis Hukum Perdata atas Perjanjian Jual Beli Usaha Mikro, Kecil, dan Menengah (UMKM) Melalui Pesan Singkat - Churniawan, Mohammad Bagus Feri; Muis, Lidya Shery (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid digital transformation in business practices has led to the widespread use of short messaging applications, such as WhatsApp, for conducting sales transactions among Micro, Small, and Medium Enterprises (MSMEs). Specific Background: However, the absence of clear legal frameworks for agreements made through these digital platforms often causes disputes and losses for MSME actors. Knowledge Gap: Limited understanding of the legal validity and consumer protection mechanisms within electronic contracts creates uncertainty in enforcing rights and obligations. Aims: This study aims to examine the civil law validity of sale and purchase agreements made via short messages and evaluate the legal protection available for MSMEs in Indonesia. Results: Findings reveal that transactions through messaging applications are legally valid if they fulfill the conditions outlined in Articles 1313 and 1320 of the Indonesian Civil Code. MSMEs are entitled to compensation when receiving non-compliant goods, yet most lack awareness of claim procedures. Novelty: The study provides a legal framework linking electronic contracts and traditional civil law concepts in the MSME digital context. Implications: Strengthening MSME legal literacy and ensuring transparent electronic contracting processes are crucial to prevent contractual disputes. <article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:51644add-6e80-411c-9b06-eb2ca121fe82-10" data-testid="conversation-turn-4" data-scroll-anchor="false" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="dab72f55-e430-4725-8eb2-34e2a6c2ea78" data-message-model-slug="gpt-5"> Highlights: Legal validity of WhatsApp-based contracts under civil law. MSME rights to compensation for non-compliant goods. Integration of civil law principles with digital trade practices. Keywords: Civil Law, MSMEs, Electronic Contract, Consumer Protection, WhatsApp Transactions